Feasibility of a facile butanol bioproduction using planetary mill pretreatment. (January 2016) - Kwon, Jeong Heo; Kang, Hyunsoo; Sang, Byoung-In; Kim, Yunje; Min, Jiho; Mitchell, Robert J.; Lee, Jin Hyung
Highlights: Convenient butanol production method proposed using planetary mill pretreatment. Planetary mill pretreatment eliminates need for biomass washing and buffer changes. Planetary milled Pinus rigida hydrolysates utilized directly without detoxication. Improved biobutanol yields with sugars from the hydrolysates than purified glucose. Abstract: A facile butanol bioproduction process was developed using planetary milling, and Pinus rigida wood waste as a model substrate for fermentable sugars. The use of planetary milling as the pretreatment eliminates the need for washing and transfer of the biomass prior to enzymatic hydrolysis. Moreover, using this pretreatment process resulted in the production of only 0.072 ± 0.003 g/L soluble phenolic compounds, a concentration that was not inhibitory towards Clostridium beijerinckii NCIMB 8052. As the milling was performed in a compatible buffer (50 mM acetate, pH 4.8), the enzymatic hydrolysis step was initiated by simply adding the cellulase cocktail powder directly to pretreated biomass without washing the biomass or exchanging the buffer, resulting in a glucose yield of 31 g/L (84.02%). Fermentation of the hydrolysate samples by C. beijerinckii NCIMB 8052 gave slightly better butanol yields than cultures grown in a typical lab media (P2), with final concentrations of 6.91and 6.66 g/L, respectively.